From intercultural to transcultural communication. (4th May 2022) - Baker, Will
ABSTRACT: The fluidity of communicative practices in current intercultural communication research raises difficult questions about how we understand core concepts in the field. Links between linguistic resources, other modes, and cultures are created in situ suggesting that relationships between 'named' languages and cultures cannot be taken for granted. We frequently see emergent cultural practices and references which are neither part of any one culture or, crucially, necessarily in-between cultures. Thus, the traditional metaphor of 'inter' for intercultural communication is no longer adequate and such communication is better approached as transcultural communication where borders are transcended, transgressed and in the process transformed.